Ketogenic diets are not beneficial for athletic performance - Burke, L. M.; Whitfield, J. (Medicine & Science in Sports & Exercise, 2024)
We write as sports scientists who support elite endurance athletes, defining endurance sports as competitions of >30 min duration where success is determined by an athlete`s ability to sustain the highest power outputs/speed, for the event duration or at critical moments. Although many factors contribute to performance, the availability of muscle fuels and the integration of their optimal use have dominated sports nutrition interests for a century (1). Unsurprisingly, endurance athletes have focused on key attributes of carbohydrate (CHO) metabolism: its rapid activation, provision of an oxygen-independent pathway for adenosine triphosphate production, and 5%-7% greater adenosine triphosphate yield per liter of oxygen consumed in its oxidative pathway compared with fat (2). Therefore, the ground-breaking 1983 paper by Phinney et al. (3) demonstrating that massive reserves in muscle capacity for fat oxidation, even in endurance-trained athletes, could be unlocked by 4 wk of ketogenic low-CHO high-fat (LCHF) intake, challenged contemporary beliefs about the absolute importance of muscle glycogen utilization during prolonged moderate-intensity exercise. Curiously, there was no association between the improvements in exercise capacity and the increase in fat oxidation (glycogen sparing) in these cyclists (3), suggesting other explanations for the observed changes in endurance; these include day-to-day variability and training-induced changes that were amplified by the order effect in the study protocol (all cyclists undertook the LCHF trial as their second trial). Most importantly, however, we were unable to find a home for this strategy within our domain because of the coincidental discovery that "... the price paid for the conservation of CHO during exercise appears to be a limitation of the intensity of exercise that can be performed … a throttling of function near VO2max" (3).